1977
DOI: 10.1136/jnnp.40.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Reticular reflex myoclonus: a physiological type of human post-hypoxic myoclonus.

Abstract: SUMMARY A patient with post-hypoxic myoclonus, sensitive to therapy with 5-hydroxytryptophan and clonazepam, was subjected to detailed electrophysiological investigation. Brief generalised jerks followed the critical stimulus of muscle stretch. The electroencephalogram showed generalised spikes that were associated with, but not time locked to, the myoclonus. The cranial nerve nuclei were activated upward. Analysis of the findings suggests that the mechanism of the myoclonus is hyperactivity of a reflex mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
105
3

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(117 citation statements)
references
References 6 publications
9
105
3
Order By: Relevance
“…The general hypothesis is that damage to the brainstem is worse in terms of prognosis compared to cortical lesions in PAE 1, 7. Generalized myoclonus has been associated with a subcortical origin,7, 8, 9, 10, 11 however in this study we showed that generalized PHM can be of cortical origin as well. Interestingly, Gentsch and colleagues (2015) found that the total amount of brain damage predicts outcome in PAE 36.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The general hypothesis is that damage to the brainstem is worse in terms of prognosis compared to cortical lesions in PAE 1, 7. Generalized myoclonus has been associated with a subcortical origin,7, 8, 9, 10, 11 however in this study we showed that generalized PHM can be of cortical origin as well. Interestingly, Gentsch and colleagues (2015) found that the total amount of brain damage predicts outcome in PAE 36.…”
Section: Discussioncontrasting
confidence: 46%
“…However, meanwhile, via the corpus callosum the contralateral motor cortex is activated as well (interhemispheric excitation spread), finally effectively producing a bilateral generalized jerk 33, 34, 35. Certainly, generalized PHM can arise from the brainstem 8. However, it is not clear if in every case damage to the brainstem is causative for its manifestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One particular examination finding of prognostic importance is early posthypoxic myoclonus (PHM). Early PHM is defined clinically by focal, multifocal, or generalized myoclonic movements of the face, trunk, extremities, and sternocleidomastoid and trapezius muscles that begin within 72 hours of CRA (3)(4)(5)(6)(7)(8). Early PHM arises due to brain injury and subsequent increased neuronal hyperactivity (3,5,6).…”
mentioning
confidence: 99%